Self-harm among college students: an epidemiological and qualitative analysis - Hoyt, Wendy D., author; Hamilton, Scott B., advisor; Cropanzano, Russell, committee member; Rickard, Kathryn M., committee member; Anderson, Jennifer, committee member (Colorado State University. Libraries, 2002)
To date, research regarding cutting, its prevalence, etiology and comorbidity with other behaviors has been limited, particularly with respect to college student populations. In addition, existing research has failed to identify intervention strategies that are consistently effective in the treatment of cutting. Thus, two studies examining cutting were conducted in order to determine 1) the prevalence of cutting on a large college campus, 2) the comorbidity of cutting with disordered eating, substance use, depression and abuse/neglect, 3) utilization of campus treatment options, 4) phenomenological aspects, and 5) interviewees' perceptions of what interventions were most helpful in their recovery. These issues were addressed through a two-stage process consisting of an epidemiological study of a large college campus, and interviews with 9 college-aged students engaging in cutting. In the first stage, a total of 1941 of 4000 surveys mailed to randomly selected undergraduate students were returned. Results indicated that there was an overall prevalence rate of 11.6% for cutting, with 12.0% of female and 11.0% of male respondents reporting a history of cutting. Results also indicate that there is a higher prevalence of disordered eating, history of abuse, and depression in those with a history of cutting. Less than 5% of participants indicated having ever utilized campus treatment options. The second stage of the current study involved a grounded theory qualitative analysis of interviews with 7 females and 2 males. The proposed theory maintains that those who engage in cutting do so as a result of overwhelming, intolerable, difficult emotions. The act of cutting is followed by both positive and negative personal reactions, which led participants to engage in both hiding their cutting from others and seeking help; consequences of these strategies had an effect on future cutting episodes. The epidemiological and qualitative studies together indicate that cutting, and its related behaviors, significantly affect at least 10-12% of the college student population, and that very few of these college students seek help. Thus, it is evident that greater awareness on the part of college campus communities, particularly those agencies designed to provide treatment to college students, is needed.
Keywords: psychotherapy; behavioral sciences; behavioral psychology; clinical psychology